PENERAPAN METODE BENFORD’S LAW MENDETEKSI INDIKASI FRAUDULENT FINANCIAL STATEMENT PERUSAHAAN ASURANSI JIWA INDONESIA TAHUN 2020-2023 - Suhaidar; Julia; Putri, Nur Intani Ramadina (STIE Mahardhika, 2024)
The increasing public interest in conventional life insurance in Indonesia presents a paradox with the rise of fraud cases over the past two decades, highlighting the need for effective fraud detection in life insurance companies. This study aims to detect indications of fraudulent financial statements in life insurance companies in Indonesia from 2020 to 2023 using the Benford's Law detection method. The dependent variable is fraudulent financial statements, and the independent variable is the Benford's Law detection method. The research employs purposive sampling, resulting in 36 samples. The data used are secondary data obtained from financial and annual reports downloaded from the OJK and related company websites. Data analysis involves data profiling, descriptive statistics, and main testing on the first and second digits. Conformity tests include the z-statistic, chi-square, and MAD tests using SPSS 26 and Microsoft Excel 2016. The results indicate a significant difference between the frequencies of the first and second digits in the financial reports of life insurance companies in Indonesia from 2020 to 2023. While the chi-square test shows no significant difference, the z-statistic and MAD tests indicate that the differences are significant and valid as accounting anomalies, suggesting the potential occurrence of fraudulent financial statements.